The essential Deming : leadership principles from the father of total quality - Deming, W. Edwards [ (William Edwards)] , 1900-1993; Orsini, Joyce Nilsson (McGraw-Hill, 2013)
Offers articles, papers, lectures, and notes touching on a wide range of topics, but which focus on the author's overriding message: quality and operations are all about systems, not individual performance; the system has to be designed so that the worker can perform well